Uterine histomorphological and immunohistochemical investigation during the follicular phase of estrous cycle in Saidi sheep - Mahmoud Abd-Elkareem; Mohsen A. Khormi; Mohammed A. Alfattah; Mervat S. Hassan (BMC Veterinary Research)
Abstract Background Saidi sheep are one of the most important farm animals in Upper Egypt, particularly in the Assiut governorate. Since they can provide meat, milk, fiber, and skins from low-quality roughages, sheep are among the most economically valuable animals bred for food in Egypt. Regarding breeding, relatively little is known about the Saidi breed. In mammals, the uterus is a crucial reproductive organ. Therefore, the purpose of this work was to provide further details on the histological, histochemical, and immunohistochemical analyses of superoxide dismutase 2 (SOD2), glutathione reductase (GR), and progesterone receptor alpha (PRA) as well as terminal deoxynucleotidyl transferase (TdT) dUTP nick-end labeling assay (TUNEL) of the uterus during the follicular phase of estrous cycle in Saidi sheep. Thus, 11 healthy Saidi ewes (38.5 ± 2.03 kg weight) ranging in age from 2 to 5 years were used to examine the histological changes in the uterus. Results In Saidi sheep, the uterine histological and immunological picture during the follicular phase of the estrous cycle was characterized by epithelial and stromal proliferation and apoptosis. Leucocytic recruitment (lymphocytes, plasma, and mast cells) was also observed. Uterine gland adenogenesis, vascular angiogenesis, oxidative marker expression, and PRA expression in the muscles, stroma, and epithelium were the most noticeable features of the follicular phase. Conclusion This study provides new evidence of the role of PRA, SOD2, GR, and mast cells in controlling uterine epithelial proliferation and apoptosis in the Saidi sheep during the follicular phase of the estrus cycle. These findings have growing significance in understanding the key mechanisms that characterize successful reproduction and enhancing the fertility and reproductive efficiency in Saidi Sheep.